Mortality associated with heart failure with preserved vs. reduced ejection fraction in a prospective international multi-ethnic cohort study. (29th January 2018) - Lam, Carolyn S P; Gamble, Greg D; Ling, Lieng H; Sim, David; Leong, Kui Toh Gerard; Yeo, Poh Shuan Daniel; Ong, Hean Yee; Jaufeerally, Fazlur; Ng, Tze P; Cameron, Vicky A; Poppe, Katrina; Lund, Mayanna; et al.
Abstract: Aims: Whether prevalence and mortality of patients with heart failure with preserved or mid-range (40–49%) ejection fraction (HFpEF and HFmREF) are similar to those of heart failure with reduced ejection fraction (HFrEF), as reported in some epidemiologic studies, remains highly controversial. We determined and compared characteristics and outcomes for patients with HFpEF, HFmREF, and HFrEF in a prospective, international, multi-ethnic population. Methods and results: Prospective multi-centre longitudinal study in New Zealand (NZ) and Singapore. Patients with HF were assessed at baseline and followed over 2 years. The primary outcome was death from any cause. Secondary outcome was death and HF hospitalization. Cox proportional hazards models were used to compare outcomes for patients with HFpEF, HFmrEF, and HFrEF. Of 2039 patients enrolled, 28% had HFpEF, 13% HFmrEF, and 59% HFrEF. Compared with HFrEF, patients with HFpEF were older (62 vs. 72 years), more commonly female (17% vs. 48%), and more likely to have a history of hypertension (61% vs. 78%) but less likely to have coronary artery disease (55% vs. 41%). During 2 years of follow-up, 343 (17%) patients died. Adjusting for age, sex, and clinical risk factors, patients with HFpEF had a lower risk of death compared with those with HFrEF (hazard ratio 0.62, 95% confidence interval 0.46–0.85). Plasma (NT-proBNP) was similarly related to mortality in both HFpEF, HFmrEF, and HFrEF independent of the co-variates listed and of ejection fraction. Results were similar for the composite endpoint of death or HF and were consistent between Singapore and NZ. Conclusion: These prospective multinational data showed that the prevalence of HFpEF within the HF population was lower than HFrEF. Death rate was comparable in HFpEF and HFmrEF and lower than in HFrEF. Plasma levels of NT-proBNP were independently and similarly predictive of death in the three HF phenotypes. Trial Registration: Australian New Zealand Clinical Trial Registry (ACTRN12610000374066).